The rice soils of cambodia. I. Soil classification for agronomists using the cambodian agronomic soil classification system - White, P.; Dobermann, A.; Oberthür, T.; Ros, C. (Wiley, 2000)
. This paper describes a soil classification system developed for agronomists in Cambodia that has proved useful in improving soil fertility management. The classification system relies on soil characteristics that are easily identifiable in the field and have agronomic relevance. The system was used in the on‐farm trial programme of the Cambodia‐IRRI‐Australia Project (CIAP) in 1996 and 1997 to determine whether it could adequately discriminate between soil types and improve fertility management.  Using diagnostic criteria that could be identified in the field, 11 soil groups were defined and subdivided into a further 20 phases. Soil groups were defined as units of morphologically similar soils, which occurred at the same position in the landscape. Classification of soil phases within a soil group was primarily based on soil properties that had significance for crop production, this included information gained from local experience and expertise. A modified version of the Fertility Capability Classification (Sanchez et al., 1982) was added as a third level to allow a more quantitative classification in cases where soil analytical data was available, and to facilitate the transfer of agronomically important soil information from outside Cambodia.  The soil groups adequately predicted differences in grain yields of rice grown on the different soils in on‐farm trials and provided the basis for soil‐specific management recommendations. Local agronomists have welcomed the system and have incorporated it into their research and extension operations.